Drought- and heatwave-associated compound extremes: A review of hotspots, variables, parameters, drivers, impacts, and analysis frameworks - Afroz, Mahnaz; Chen, Gang; Anandhi, Aavudai (Frontiers in Earth Science, 2023)
Droughts and heatwaves are among the rising concerns with regards to the frequent formation of compound or concurrent extremes (CEs), which have the potential to cause greater havoc than an individual event of a higher magnitude. Recently, they have been frequently detected forming CEs together or with other events (i.e., floods, aridity, and humidity events) concurrently or with spatiotemporal lags. Therefore, this systematic review assesses these CEs by reviewing the following aspects: CE hotspots, events, and variable combinations that form CEs; frequently analyzed CE parameters (i.e., frequency and severity); large-scale modes of climate variability as drivers alongside the approaches to relate them with CEs; and impacts of CEs (i.e., yield loss and fire risk) alongside impact integration approaches from 166 screened publications. Additionally, three varied analysis frameworks of CEs are summarized to highlight the different analysis components of drought- and heatwave-associated CEs, which is the novelty of this study. The analysis frameworks vary with regards to the three major assessment objectives, namely only CE parameters (event-event), driver association (event-driver), and impacts (event-impact). According to this review, the most frequently reported hotspots of these CEs in global studies are southern Africa, Australia, South America, and Southeast Asia. In regional studies, several vital hotspots (e.g., Iberian Peninsula, Balkans, and Mediterranean Basin) have been reported, some of which have not been mentioned in global studies because they usually report hotspots as broader regions. In addition, different event combinations (i.e., drought and heatwave; and heatwave and stagnation) are analyzed by varying the combination of s, namely temperature, precipitation, and their derived indices. Thus, this paper presents three major analysis frameworks and components of drought- and heatwave-associated CE analysis for prospective researchers.